Developing a Problem-Based Learning Textbook for Al-Kitabah Al-‘Ilmiyyah at the University Level - Zawawi, Moh; M. Abdul Hamid; Sutaman, Sutaman; Khoirul Huda; Abdul Wahab Naf’an (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
Research and development model research is essential to meet the quality of coursebooks. This study aimed to develop al kitabah al ilmiyyah textbooks based on problem-based learning and measure their effectiveness. The research adopted Borg and Gall’s model, which includes seven stages: needs analysis, planning, initial product development, product validation, product revision, product trials, and final product refinement after field testing. The study employed both qualitative and quantitative descriptive methods. Data were collected through questionnaires, observations, and interviews, and analyzed using validation testing techniques. The findings indicate that the development of the al-Kitābah al-‘Ilmiyyah textbook was effective, as demonstrated by improvements in pre-test and post-test scores in both the control and experimental groups. The experimental group showed a higher average post-test score than the control group, suggesting the textbook's positive impact.